2012
DOI: 10.1080/00221341.2012.674546
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Qualitative Research: Experiential Learning in Group-Based Interviews and Coding Assignments

Abstract: This article describes experiential-learning approaches to conveying the work and rewards involved in qualitative research. Seminar students interviewed one another, transcribed or took notes on those interviews, shared those materials to create a set of empirical materials for coding, developed coding schemes, and coded the materials using those schemes. Students' input reveals that these assignments were more effective than readings and discussions in conveying the challenges and rewards of qualitative resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 41 publications
(61 reference statements)
0
21
0
Order By: Relevance
“…Learners' self-reflexive writing can also provide teachers with rare insights into students' (pre)conceptions, anxieties or motivations as novice researchers. In one notable development of students' reflective practice, the teacher went as far as to co-author an article on the teaching and learning of research methods for a major peer-reviewed journal with nine of her students (DeLyser et al, 2012). While reflexive writing typically requires students to pay critical attention to their own research practice, instructors have also found innovative ways of using existing interview data to explore how positionality, tension and sensitivity play out in the research of others (Hsiung, 2008).…”
Section: Reflection On the Research Processmentioning
confidence: 99%
See 3 more Smart Citations
“…Learners' self-reflexive writing can also provide teachers with rare insights into students' (pre)conceptions, anxieties or motivations as novice researchers. In one notable development of students' reflective practice, the teacher went as far as to co-author an article on the teaching and learning of research methods for a major peer-reviewed journal with nine of her students (DeLyser et al, 2012). While reflexive writing typically requires students to pay critical attention to their own research practice, instructors have also found innovative ways of using existing interview data to explore how positionality, tension and sensitivity play out in the research of others (Hsiung, 2008).…”
Section: Reflection On the Research Processmentioning
confidence: 99%
“…To conceive of the learning of research methods as reflexive may involve learners reflecting critically upon their research practice, on the methods they are being taught and on the socio-cultural context within which learning is taking place. Once again, the language of reflexivity was used only in a small number of the papers we reviewed (DeLyser, 2008;DeLyser et al, 2012;Thien, 2009), although approaches that encouraged reflection on the research process as part of students' learning were discussed more widely.…”
Section: Reflection On the Research Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Interview data, member checking data, interview protocols, and transcribe notes are filed in the participant folder. Using labels or codes is to protect each participant's confidentiality [82]. Vohra (2014) [83] used codes and labels to organize the data, explore patterns, and generate themes before data analysis.…”
Section: Data Organization Techniquesmentioning
confidence: 99%